2014
DOI: 10.4317/medoral.19071
|View full text |Cite
|
Sign up to set email alerts
|

Molecular markers of cell adhesion in ameloblastomas. An update

Abstract: Ameloblastoma is the most common odontogenic tumor of epithelial origin, and though it is of a benign nature, it frequently infiltrates the bone, has a high rate of recurrence and could potentially become malignant. Cellular adhesion potentially plays an important role in the manifestation of these characteristics and in the tumor biology of ameloblastomas. Losses of cell-cell and extracellular matrix adhesion and cohesion are among the first events that occur in the invasion and growth of tumors of epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 39 publications
0
15
0
1
Order By: Relevance
“…Cell adhesion molecules are altered in various neoplasms, especially malignant ones, favoring progression, invasion, recurrence, and metastasis [3, 30]. Ecad is a molecule with tumor suppressor functions; it is possible that these functions are related to the capacity of cells to adhere because in normal cells, growth and migration are inhibited when one cell adheres to another [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell adhesion molecules are altered in various neoplasms, especially malignant ones, favoring progression, invasion, recurrence, and metastasis [3, 30]. Ecad is a molecule with tumor suppressor functions; it is possible that these functions are related to the capacity of cells to adhere because in normal cells, growth and migration are inhibited when one cell adheres to another [30].…”
Section: Discussionmentioning
confidence: 99%
“…The loss of cellular adhesion plays an important role in the invasion and growth of tumor cells which are among the first events that occur in tumors of epithelial origin, such as ameloblastomas [3]. E-Cadherin (Ecad) is a calcium-dependent cell adhesion molecule that is expressed in epithelial tumors and is associated with prognosis; reduced or eliminated Ecad expression is associated with progression, invasion, and a poor prognosis in these types of tumors [47].…”
Section: Introductionmentioning
confidence: 99%
“…It is expressed on the surface of all epithelial and plasma cells, participating on adhesions between cells, or cells and extracellular matrix. 18,20,21 Syndecan-1 is abundant in the membrane of basal and supra-basal cells of normal epithelium of the skin and mucosa and its increased expression is induced during keratinocyte differentiation. 20,22 This study showed syndecan-1 (CD138) and CK14 expression in the basal and supra-basal layers of oral verruciform xanthoma, but it was, as expected, negative on the foam cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in tumors, loss of syndecan-1 is related to aggressiveness, and associated with the activation of growth factors. 20,21 It is speculated that the A) The superficial keratinocytes exhibits highly eosinophilic cytoplasm with small peripheral intracytoplasmic vacuoles and pycnotic central nuclei, depicting the microscopical orange-colored appearance (hematoxylin/eosin, ×400). The superficial parakeratinized layer exhibited (B) a characteristic CD138 positivity in a granular membrane pattern, and (C) was negative for CK14 (immunoperoxidase, ×400).…”
Section: Discussionmentioning
confidence: 99%
“…Others reported unusual rare sites of metastasis including vertebrae, skull, small bowel, brain, kidneys and heart [6,8,10]. The potential to metastasize has not correlated with histologic subtype or pattern [5] while the molecular signature of ameloblastoma that leads to metastasis is still unclear [12,13]. The exact events in the metastasis cascade of MetAm are elusive.…”
Section: Metastasizing Ameloblastomamentioning
confidence: 99%